Nrf2-mediated anti-inflammatory polarization of macrophages as therapeutic targets for osteoarthritis - Wang, Lin; He, Chengqi (Frontiers in Immunology, 2022)
Macrophages are the most abundant immune cells within the synovial joints, and also the main innate immune effector cells triggering the initial inflammatory responses in the pathological process of osteoarthritis (OA). The transition of synovial macrophages between pro-inflammatory and anti-inflammatory phenotypes can play a key role in building the intra-articular microenvironment. The pro-inflammatory cascade induced by TNF-α, IL-1β, and IL-6 is closely related to M1 macrophages, resulting in the production of pro-chondrolytic mediators. However, IL-10, IL1RA, CCL-18, IGF, and TGF are closely related to M2 macrophages, leading to the protection of cartilage and the promoted regeneration. The inhibition of NF-κB signaling pathway is central in OA treatment via controlling inflammatory responses in macrophages, while the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway appears not to attract widespread attention in the field. Nrf2 is a transcription factor encoding a large number of antioxidant enzymes. The activation of Nrf2 can have antioxidant and anti-inflammatory effects, which can also have complex crosstalk with NF-κB signaling pathway. The activation of Nrf2 can inhibit the M1 polarization and promote the M2 polarization through potential signaling transductions including TGF-β/SMAD, TLR/NF-κB, and JAK/STAT signaling pathways, with the regulation or cooperation of Notch, NLRP3, PI3K/Akt, and MAPK signaling. And the expression of heme oxygenase-1 (HO-1) and the negative regulation of Nrf2 for NF-κB can be the main mechanisms for promotion. Furthermore, the candidates of OA treatment by activating Nrf2 to promote M2 phenotype macrophages in OA are also reviewed in this work, such as itaconate and fumarate derivatives, curcumin, quercetin, melatonin, mesenchymal stem cells, and low-intensity pulsed ultrasound.